Supervising Teacher’s Perceptions on In-Service Teacher Certification Program (PPG Dalam Jabatan) - Fadilah Zunuaris; Yetti Zainil (Journal of English Language Teaching, 2021)
In order to be professional, a teacher needs to master teacher competencies, so the teacher will achieve their work clearly and effectively. To be approved as a professional, initially, a teacher should join in-service teacher certification program (PPG dalam jabatan). This program has a goal to improve the teacher’s professionalism, later they will obtain a certificate. Nonetheless, there are still teachers proven lacking of teacher competencies according to the result of 2018 Teacher Competency Test (Uji Kompetensi Guru). Besides, although this program has been conducted for several years in English department of Universitas Negeri Padang, but the issues related to this matter have not been analysed yet. Hence, the supervising teachers’ perceptions toward this program were needed since they have guided the in-service teachers practicing teacher practice at schools. A questionnaire consisted of two types of questions were given to get the supervising teachers’ perception toward in-service teacher certification program. Overall, according to the results, the supervising teachers gave positive feedbacks, albeit there were some negative perceptions found. It is found that the English teachers were capable the most at personal competency. Also, it is evidenced that the English teachers’ pedagogical and professional competency are indeed still low affecting their capability at administering in practicing teacher practice.